PS 07-28 GAMMA/DELTA T CELLS MEDIATE ANGIOTENSIN II-INDUCED HYPERTENSION AND VASCULAR INJURY. (September 2016) - Caillon, Antoine; Mian, Muhammad Oneeb Rehman; Fraulob-Aquino, Julio C.; Huo, Kugeng; Barhoumi, Tlili; Paradis, Pierre; Schiffrin, Ernesto L.
Abstract : Objective: Both innate antigen-presenting cells and the adaptive immune system have been shown to play a role in the development of hypertension. Nevertheless, the T cell subsets involved in the pathophysiology of hypertension remains unclear. There is a small subset of "innate-like" T cells expressing the g/d T cell receptor (TCR) rather than the a/b TCR that could play a role bridging between the innate and adaptive immune systems. However, it is unknown whether g/d T cells contribute to the development of hypertension. We hypothesized that angiotensin (Ang) II-induced hypertension and vascular injury would be blunted in Tcrd −/− mice, which are devoid of g/d T cells. Design and Method: Thirteen to 15-week old male C57BL/6 wild-type and Tcrd −/− mice were infused or not with Ang II (490 ng/kg/min, SC) for 7 or 14 days. Telemetric blood pressure (BP), mesenteric artery endothelial function and vascular remodeling by pressurized myography, and spleen T cell profile by flow cytometry were evaluated. Results: Fourteen days of Ang II increased systolic BP by 42 mmHg ( P  < 0.01) in wild-type compared to control mice. The frequency of g/d T cells (2.3-fold, P  < 0.05) and activated (CD69+) g/d T cells (1.6-fold) was increased after 7 days of Ang II, and 7 days later remained increased or rose further (2.4-fold) in wild-type compared to control mice. Ang II decreased mesenteric artery relaxation responses to acetylcholine by 42% ( P  < 0.01) and increased media/lumen by 45% ( P  < 0.01) in wild-type mice compared to controls. BP rise and all the above mentioned Ang II effects were abrogated in Tcrd −/− mice. Conclusions: These data suggest that g/d T cells mediate Ang II-induced BP elevation and vascular injury. g/d T cells could be key immune cells bridging innate and adaptive immune responses during the development of hypertension in mouse models and by extension in humans.